Pengendalian Sosial Kejahatan (Suatu Tinjauan Terhadap Masalah Penghukuman Dalam Perspektif Sosiologi) - Mas Ahmad Yani (Jurnal Cita Hukum, 2015)
Abstract: Social Control of Crimes. Embodiments may include criminalization of social control, compensation, treatment or conciliation. The standard punishment is a ban which, if violated, will result in suffering for those who violate the provision of criminal sanctions against the perpetrators. On compensation, standard or benchmark is an obligation, where the initiative for the process is on the injured party / victim, where the injured party will request compensation (in the civil suit), because the opponent did injury appointment or committed an unlawful act ( on rechtmategedaad). Here there are losers and winners, so as with punishment, nature is akuisator (forced). Unlike the process of punishment and compensation, then the therapeutic or remedial nature means conciliation aims to restore the situation to its original state as recapitalization, debt restructuring, reskeduling can be included in this category. The default is the normality and harmony or harmony. In the form of therapy, the victim took the initiative to improve himself with the help of certain parties, for example assistance consulting services.  Abstrak: Perwujudan pengendalian sosial dapat berupa pemidanaan, kompensasi, terapi atau konsiliasi. Standar atau patokan pemidanaan adalah suatu larangan yang apabila dilanggar, akan mengakibatkan penderitaan bagi pelanggarnya berupa pemberian sanksi pidana terhadap pelakunya. Pada kompensasi, standar atau patokannya adalah kewajiban, di mana inisiatif untuk memprosesnya ada pada pihak yang dirugikan/korban, di mana pihak yang dirugikan akan meminta ganti rugi (dalam proses gugatan perdata), karena pihak lawan melakukan cedera janji atau melakukan perbuatan melawan hukum (on rechtmategedaad). Di sini ada pihak yang kalah dan yang menang, sehingga seperti halnya dengan pemidanaan, sifatnya adalah akuisator (dipaksa). Berbeda dengan proses pemidanaan dan kompensasi, maka terapi maupun konsiliasi sifatnya remedial artinya bertujuan mengembalikan situasi pada keadaan semula seperti rekapitalisasi, restrukturisasi utang, reskeduling dapat dimasukkan dalam katagori ini. Standarnya adalah normalitas dan keserasian atau harmoni. Pada bentuk terapi, korban mengambil inisiatif sendiri untuk memperbaiki dirinya dengan bantuan pihak-pihak tertentu, misalnya bantuan jasa konsultan.  Kata Kunci: Pengendalian Sosial, Kejahatan, Penghukuman.DOI: 10.15408/jch.v2i1.1842